The Relationship of Perceived Career Development, Work Motivation, and Performance: a Study among ASN that the Organization Has Changed the Echelon - Luxmaning Hutaki Widiastari; Arum Etikariena (Budapest International Research and Critics University, 2022)
The purpose of this study determined the mediating role of work motivation on the relationship between perceived career development and the performance of the State Civil Apparatus whose agency equalized structural/echelon positions into functional positions. This study is a quantitative study using a self-report questionnaire via an online form. Respondents are Employee Government/ASN aged 25-56 years taking into account education, years of service, and the current position selected by convenience sampling. The analysis was carried out using Mediation Model 4 from Process v4.0 by Andrew Hayes on IBM SPSS version 26. After measuring, each variable measuring instrument achieved good and valid reliability. The direct effect of perceived career development on ASN performance was greater (effect value = 0.0818; p < 0.005; LLCI = 0.0482 and ULCI = 0.1154) than the direct effect mediated by work motivation (effect value = 0.0686; p < 0.005; LLCI=0.0449 and ULCI=0.0932). This shows that work motivation partially mediates the relationship between perceived career development and ASN performance significantly. Furthermore, from the results of this study, government agencies that carry out structural/echelon position equalization can develop programs that can improve the career development perceived by ASN and work motivation to improve ASN performance.